Pemantauan Penanganan Longsoran Badan Jalan dengan Drainase Horisontal - Haliena Armela (Direktorat Bina Teknik Jalan dan Jembatan, 2005)
One of the alternative technologies for landslide handling is a horizontal drainage. Development of this technology has been started since 1997 with full scale trial model of line perforation type and hole perforation type for several depth variations at the road Cikalong – Cariu Km 4+725 (Cariu) which constitute as an alternative track between Jakarta – Bandung. The objective of this handling was to reduce the water level of the land from slope of road and to identify the effectivity of the landslide handling. The problem of landslide was the road depression of 35 m. Analysis of the monitoring data showed that ground water surface has degraded for 0.005 m (at external field of slide area) and 0.105 m (at the slide area), pore water pressure has degraded for 0.2 mH2O on line 1 and 0.71 mH2O (at the slide area), water flowrate released on horizontal drainage outlet of hole perforation type was 0.011 to 2.42 L/day, higest than the line perforation type, land surface movement happened on the main and base slide was 0.1 to 1.1 cm. Monitoring result of landslide handling with this construction was quite effective to be applied to landslide problem on slope slide and road segment with ground water (water table) factor which uncontrolled on permeable soil. The type of perforation pipe which is more effective to be used is a hole type